Removal of Ampicillin Resistance Genes using Activated Carbon in Drinking Water Treatment: Penghilangan Ampicillin Resistance Genes dengan Karbon Aktif pada Pengolahan Air Bersih - Sri Anggreini; Ade Jaya Saputra; Syaiba Suci Ramadhini (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2026)
The presence of antibiotic resistance genes (ARGs) in raw water has become a major concern in water treatment due to their role in accelerating the spread of antimicrobial resistance. Conventional treatment processes are often unable to effectively remove these genetic contaminants. This study aimed to evaluate the adsorption behavior and capacity of plasmid-encoded ampicillin resistance genes (ampR) using various types of activated carbon. Batch adsorption experiments were conducted using ten types of activated carbon, consisting of five coal-based and five wood-based carbons. Adsorption kinetics were analyzed using pseudo-first-order and pseudo-second-order models. The results showed that ampR adsorption on activated carbon followed the pseudo-second-order model. The adsorption rate constants ranged from 8.10 × 10⁻¹² to 6.19 × 10⁻¹¹ copies mg⁻¹ min⁻¹ for coal-based activated carbon and from 3.32 × 10⁻¹¹ to 2.66 × 10⁻¹⁰ copies mg⁻¹ min⁻¹ for wood-based activated carbon. The findings demonstrate that activated carbon has strong potential as an adsorbent for removing ampR in water treatment systems and support the development of more effective water treatment technologies.